Nature, Habit and Education of Passions - Rodríguez Valls, Francisco (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
This paper deals with a study of passion as a necessary element to understand human being´s substantial unity. That is the reason of the fact that passion appears as a topic in philosophical tradition. This is researched through the analysis of two questions. Firstly, through the analysis of the concepts of nature and second nature applied passions. Secondly, it treats the conflict between passions and reason and the matter of an education of passions